Rare Causes of Musculoskeletal Pain: Thinking beyond Common Rheumatologic Diseases - Julia F. Charles; Alan O. Malabanan; Stan Krolczyk; Kathryn M. Dahir (Case Reports in Rheumatology)
Objectives. Rare metabolic bone diseases can present with symptoms mimicking more common rheumatological conditions including spondyloarthritis, osteoarthritis, and fibromyalgia. Increasing awareness of these rare diseases within the rheumatology community is vital to ensure that affected patients are diagnosed and appropriately treated. The literature includes several reports of tumour-induced osteomalacia initially diagnosed as rheumatic disease, but other rare diseases such as X-linked hypophosphatemia (XLH) and hypophosphatasia (HPP) also deserve attention. Here, we describe two cases of adult patients incorrectly diagnosed with ankylosing spondylitis and osteoarthritis who, upon referral to a metabolic bone disease specialist, were subsequently diagnosed with XLH and HPP, respectively, profoundly altering their management. Methods. The cases were collected from Brigham and Women’s Hospital, Boston, MA, USA, and Vanderbilt University Medical Center, Nashville, TN, USA. Results. Details of the patients’ respective medical and family histories are presented, and the clinical and biochemical investigations undertaken to reach the correct diagnoses are described. Conclusion. Rheumatologists should be encouraged to think beyond common rheumatological diseases when faced with symptoms such as bone pain, muscle pain, and stiffness, especially when accompanied by manifestations including atraumatic fractures, poor dentition, and hearing loss. In cases where one of these rare diseases is suspected, referral to a metabolic bone disease specialist for confirmation of diagnosis is encouraged as effective treatment options have recently become available.